Significant racial differences in the incidence and behavior of the follicular variant of papillary thyroid carcinoma. Issue 5 (16th January 2019) - Mehta, Vikas; Ow, Thomas J.; Kim, Seokhwa; Tharakan, Theresa; Schiff, Bradley; Smith, Richard V.; In, Haejin
Abstract: Background: Increased detection of papillary thyroid cancer (PTC) has led to overtreatment of the largely indolent follicular variant (fvPTC). To guide management of non‐aggressive lesions, we investigated whether race predicts PTC variant and tumor behavior. Methods: Analysis of 258 973 patients from the National Cancer Database diagnosed with PTC in 2004‐2014. Clinical and tumor information was compared by race. Multivariate logistic regression was used to predict fvPTC, extrathyroidal extension (ETE), and lymph node metastasis (LNM) of fvPTC. Results: Blacks had the highest fvPTC rate (40% vs white 30%, Hispanic 26%, Asian 25%, P < .001). Blacks had higher odds of fvPTC (aOR = 1.33, 95% CI: 1.28‐1.37) and lower odds of ETE than whites (aOR = 0.90, 95% CI: 0.82‐0.99) ( P < .001). Hispanics and Asians had lower odds of fvPTC (aOR = 0.89, 95% CI: 0.86‐0.92 and aOR = 0.81, 95% CI: 0.79‐0.84) and higher odds of LNM and ETE than whites ( P < .001). Conclusions: Racial disparities in fvPTC incidence and behavior should be considered to optimize diagnosis and treatment planning.